High-purity discrete PEG-oligomer crystals allow structural insight. - French, A; Thompson, A; Davis, B (2009)
To great (monodisperse) lengths: An improved synthesis of purer ethylene glycol (EG) oligomers allows access to 16- and 32-mers pure enough for multiple incorporation, and also to the longest (48-mer) discrete EG oligomer yet reported. The high purity enables the first crystallizations and hence the first glimpses of secondary 3(10)-helical PEG structures.